Network Governance In Waste Management At Waste Banks In Serang Municipality - Hakim, Philips; Cadith, Juliannes (Future Science, 2025)
Waste bank management in Serang City involves several interacting actors, namely government, non-government, and community actors. In its implementation, challenges remain, as evidenced by the lowest level of waste management compared to other cities in Banten Province. This study analyzes waste bank management in Serang City using network governance theory, as proposed by Klijn & Koppenjan, which emphasizes four indicators: contact, trust, information sharing, and resource exchange. This study aims to explain how actors interact and coordinate with each other in the context of waste bank management in Serang City. It employs a descriptive qualitative approach, utilizing data collection methods such as interviews, observations, and documentary studies. The data is analyzed using the Miles and Huberman model. The findings show that network governance in waste bank management in Serang City is not yet optimal. It is due to the Environmental Agency's lack of contribution in providing training and technical guidance to waste bank actors. The discussion on the benefits of concern among actors is not comprehensive, and opportunistic behaviors and low community participation persist in waste sorting and management. The scope of information is inadequate, and the quality of the information supplied by the DLH to all actors is uneven. Additionally, the distribution of resources among actors is uneven, suggesting that the exchange of resources among them is not comprehensive. These findings indicate the need to enhance collaboration, strengthen capacity among stakeholders, broaden the scope of information, and optimize resource exchange to achieve optimal waste bank management in Serang City.